Evaluating Existing Mobile Apps for Toddler Parenting: Recommendations for Future App Developers - Sunita, Poonam Malik (Archives of Current Research International, 2024)
Background: As the number of smartphones in use rises, more parents are turning to mobile applications for parenting guidance. However, identifying quality apps for guidance on child development can be challenging for parents. Objective: This study evaluated existing mobile applications to disseminate important parenting information among Indian parents using a structured analysis method. Methodology: This app analysis study aimed to document the basic and special features of toddler parenting apps in India available to parents as they promote their child's development and health. To understand the accessibility and quality of apps for toddler parents, we conducted an analysis of apps in the Google Play Store. The Google Play Store was searched for available parenting apps using different search terms such as mom, mother, mommy, father, dad, papa, daddy, baby, kid, toddler, child, children, parent, and parenting. We screened 138 apps and evaluated 40 that met the criteria for their features and usability. Results: We found that a great number of toddler parenting apps are available, but most of the apps had foreign regions of origin (50%). The information is in English language (65%) and the apps are mostly non-interactive (60%). Conclusion: The study addresses a crucial gap in the availability and quality of mobile applications tailored for toddler parenting, specifically in the Indian context. By evaluating and highlighting the shortcomings of existing apps, the study provides valuable insights that can inform the development of more effective, culturally relevant, and interactive parenting tools. The findings also emphasize the need for localized content, which is vital for enhancing parenting practices and child development.